EVALUATION OF THE QUALITY OF SWEET SORGHUM FODDER - Kapustin, S.I.; Volodin, A.B.; Kapustin, A.S.; Samokish, N.V. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
According to the obtained data in 2019-2020, a plant height of the earliest variety Galiya was 201 cm, mid-season L-7897 and Tandem were 218 cm, late ripening Yarik was 282 cm. The maximum yield was obtained from the hybrid Yarik 77.0 t ha-1 of green matter and 21.5 t ha-1 of dry matter. A significant yield of green and dry matter was provided by L-7897 and Tandem. The data of the dry matter analysis show that the combinations Tandem and Yarik exceed the rates of the best standard Silosnoe 88 in terms of crude protein content and have high rates of metabolic energy. The crude fat content was similar to the standard rates. It was also found to be significant in the varieties Tandem and L-7897. The presence of crude fiber was low. The lowest rate was obtained in the hybrid Yarik. In comparison to the replaceable amino acids, the essential amino acids in the dry matter of sweet sorghum, which was cut in the milk-wax stage of ripeness, have a lower content. The average presence of essential amino acids was found in valine, phenylalanine, and argirine. Leucine had a significant rate. The maximum rates were found in the new combinations of Yarik and Tandem. Among the replaceable amino acids, the highest content had glutamic, aspartic acids, proline, alanine.